Anti-inflammatory activity of curcumin in a model of L-arginine-induced acute pancreatitis in rats - Tazeoğlu, Aybala; Özdenkaya, Yaşar; Harman Kamalı, Gülçin; Tazeoğlu, Deniz (NLM (Medline), 2023)
BACKGROUND: Acute pancreatitis (AP) is a pathology characterized by activated digestive enzymes to digest pancreatic tissue and inflammation. This study aimed to investigate the effect of curcumin, which has antioxidant and anti-inflammatory properties, on AP and its effectiveness at different doses. METHODS: Forty Sprague Dawley albino male rats, 12 weeks old, weighing 285-320 g, were used in the study. The rats were divided into control, curcumin, AP, low (100 mg/kg), and high (200mg/kg) dose curcumin groups. An experimental pancreatitis model was created with 5 g/kg L-arginine and samples (amylase, lipase, IL-1 beta, IL-6, TNF-alpha, CRP, histopathological) were taken after 72 hours. RESULTS: There was no difference between the groups in terms of the weight of the rats (p=0.76). In the AP group, it was observed that the experimental pancreatitis model was successfully created after examination. Laboratory and histopathological examination results in the curcumin-administered groups were regressed compared to the AP group. The decrease in laboratory values was higher in the high-dose curcumin group than in the low-dose (p<0.001). CONCLUSION: Laboratory and histopathological changes occur in AP according to clinical severity. The antioxidant and anti-inflammatory effects of curcumin are known. In the light of this information and according to the results of our study, it has been shown that curcumin is effective in the treatment of AP, and the effect of curcumin increases with the dose increase. Curcumin is effective in treating AP. However, while high-dose curcumin was more effective in inflammatory response than low-dose, it showed similar histopathological results.
Keywords: Acute; Curcumin; Cytokines; Inflammation; Pancreatitis